Best Answer

7x - 1 + 49x = 343

If this is what you are implying, then:

Simplify:

56x - 1 = 343

Add 1:

56x = 344

Divide by 56:

x = 344/56 = 43/7 = 6.(142857) repeating at period 6.

However, if you meant:

7(x - 1) + 49x = 343

Then divide by 7:

x - 1 + 7x = 49

Add 1:

8x = 50

Divide by 8:

x = 50/8 = 25/4 = 6.25.

Q: If 7x-1 plus 49x equals 343 then what is x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

indentity property

because boogies are in your nose

13. that's all there is to it. 7(1)+6 7+6 =13 7x1=7 7+6=13 so 13 is your answer :D

6x10+3x1+7x1/10

it means 7x1 which (as we all know it) equals 7

Related questions

indentity property

because boogies are in your nose

13. that's all there is to it. 7(1)+6 7+6 =13 7x1=7 7+6=13 so 13 is your answer :D

27.38 = 2.738*101 in standard form

its 7

6x10+3x1+7x1/10

it means 7x1 which (as we all know it) equals 7

91.737 =(9x10) + (1x1) + (7x1/10) + (3x1/100) + (7x1/1000)90 + 1 + 7/10 + 3/100 + 7/1000

7x1/2 = 7/2 = 3.5

What does N equal? Well to solve the problem you would do N+7x1, N+7x2, N+7x 3, N+7x4, N+7x5 to figure out the first five terms.

7*1=1

There are 142 of them and I have better things to do.If you really want, you can go through 7x1, 7x2 ... to 7*142.There are 142 of them and I have better things to do.If you really want, you can go through 7x1, 7x2 ... to 7*142.There are 142 of them and I have better things to do.If you really want, you can go through 7x1, 7x2 ... to 7*142.There are 142 of them and I have better things to do.If you really want, you can go through 7x1, 7x2 ... to 7*142.